Dyslexic Disorders in Students of a Young School: Peculiarities of Education and Socialization - Dandan, Li; Shaojie, Ding (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
Dyslexia is a diagnosis that is increasingly becoming a reality for students and teachers of junior high school. In the biggest part, this diagnosis becomes a surprise to both the teacher, parents, and the student because of is established in the first-second grade due to the discovery of difficulties that arise during the mastering of writing and reading. Primary school is a new step of growing up. This exciting period is often characterized by natural stress due to the lack of direct support from parents, increasing independent responsibility, competition for the teacher’s attention, and the coexistence of a large number of individuals in the team. And the difficulties arising from mastering perceiving written symbols can significantly complicate the process of socialization of the child. It creates additional barriers for the student during the formation of basic educational skills. This substantially increases anxiety and lowers the child’s self-esteem, building internal barriers and fears. The article presents the analysis of dyslexic disorder, presents its classification, and describes the probable causes of its occurrence. The authors present and characterize dyslexia’s impact on learning and socialization processes at the example of young school students. Overcoming the difficulties of mastering graphic symbols is a long and unstable process. But the authors emphasize that dyslexia is a feature, not a sentence. Children with dyslexic disorders need understanding, help from adults, and developed modern approaches to the presentation of information, increasing the level of concentration and further mastering cognitive skills. This ensures harmonious development and learning of the student and removes barriers in communication with peers, ensuring successful socialization of the child.